Desenvolvimento de microdispositivos para detecção e biorremediação de compostos fenólicos - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Contamination of aquatic environments by solid and liquid waste is a serious problem that causes damage to biodiversity. Phenolic effluents are examples of contaminants that are released into the wild without proper treatment and cause environmental disturbances, which can initiate carcinogenic processes and also cause severe damage to the central nervous system. Such compounds are often neglected in the environment at extremely high concentrations. The biological treatments and the advanced oxidative processes are the techniques that can be used degradation of these compounds, where they stand out the photodegradation having the TiO2 as catalyst and bioremediation promoted by enzymes that can be obtained from vegetables. In this way, the purpose of this work was to develop two devices, one paper-based and wax- printed, for colorimetric detection of quantification of phenolic compounds and another three- dimensional printed and coupled to lights of different luminous spectra, capable of simulating micro scale, bioremediation and photodegradation tests, also allowing synergic processes. The developed paper device presents accuracy in the detection of total phenolic compounds at concentrations of 25 mg / L and can be used as an environmental control tool. Enzymatic prospecting indicated that the fruit of the Cerrado, Philodendron bipinnatifidum is an excellent source of polyphenoloxidase (392.2 enzymatic units) with a high potential for bioremediation of phenolic compounds. The 3D device was able to simulate photodegradation and bioremediation tests of phenolic compounds, especially when such methods were applied synergistically and with the use of UV radiation where the concentration of the compound was reduced from 1000 mg / L to 301.48 mg / L (69.85%).
Keywords: Biorremediação; Fotodegradação; Polifenoloxidase; Dispositivo de papel; Dispositivo 3D; Detecção colorimétrica; Bioremediation; Photodegradation; Polyphenoloxidase; Paper device; 3D device; Colorimetric detection; Biodiversidade; Biodiversity; CIENCIAS BIOLOGICAS